Friction stir welding process parametric optimization of hybrid aluminium- bagasse ash- graphite composite by Taguchi approach. (2021) - Vignesh Kumar, P.; Paranthaman, P.
Abstract: In present work, hybrid aluminium composite was fabricated with varyingpercentage ofbagasse ash (4, 8, 12 wt%) and constant wt% of graphite (2 wt%). Friction stir welding process was adopted to assess the Weldability of developed composite. Taguchi method was adopted for experimental planning and to study the influenceof inputparameter over out response. Herein varying percentage of Tool rotation speed (1000, 1250, 1500 rpm), welding speed (3, 6, 9 mm/min)and reinforcement weight percentage are selected as input parameter and ultimate tensile strength of the welded joint was selected as output parameter. ANOVA resultsdepicts that all the inputparameter have significant over output response.